The Islamic minority in Guangzhou: history and development during the Tang Dynasty - Nurul Afifah Adila Mohd Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article aims to study the history and development of the Islamic minority in Guangzhou during the Tang Dynasty. Among the numerous dynasties in China, the Tang Dynasty stands out as one of the most prosperous in the country’s history. The prosperity of the Tang Dynasty established Guangzhou as a prominent trading centre on the Maritime Silk Road. Adopting an open-door policy, Guangzhou attracted the arrival of traders from outside the country and in 651 A.D., the influence of Islam began to spread in Guangzhou. Khalifah Uthman dispatched a delegation, led by Saad Abi Waqas, to meet Emperor Gaozong. This friendship meeting led to the on the establishment of the first and oldest mosque in Guangzhou, the Huaihseng Mosque. This study used qualitative methods, namely the collection and evaluation of data from primary and secondary sources based on historical research methods. The sources and materials referred to were obtained from the website of China Radio International (CRI) and The Guangzhou Local Chorography Department, the Chinese Islamic Association, and the ancient books of the Tang Dynasty. Library research methods involving articles, magazines, books, and newspapers were also employed. The findings show that the Muslim community in Guangzhou has a long history since the time of the Tang Dynasty. The development of the Islamic minority in Guangzhou is evidenced by the establishment of the Muslim community, the construction of the Huaisheng Mosque, the emergence of Islamic scholars, the organization of religious activities, and the appointment of religious officials. This is because the policy of the administration and economic development during the Tang Dynasty gave the opportunity for Islamic development there. This research demonstrates that the Tang Dynasty had an impact on Islamic development in China. This finding benefits the public and other researchers seeking important information on the history and development of the Islamic minority in Guangzhou, China.